1992
DOI: 10.1002/bit.260390209
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imprinting of proteins and other macromolecules resulting in new adsorbents

Abstract: When the model protein bovine serum albumin (BSA) was dissolved in a concentrated aqueous solution of the multifunctional ligand L-malic acid, the solution was lyophilized, and the solid residue thoroughly washed with tetrahydrofuran to extract malic acid, then the resultant ("imprinted") protein was capable of binding 26.4 +/-0.9 mol equivalents of the ligand in anhydrous ethyl acetate. The nonimprinted BSA (i.e., that prepared in the same manner apart from the absence of malic acid) bound less then one-tenth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 17 publications
2
33
0
1
Order By: Relevance
“…The fact that ␤-elimination is a unimolecular reaction also facilitated the kinetic analysis, and the comparison with the catalytic antibodies and the polymers. BSA was selected for initial experiments as it was available in large quantities, inexpensive, and was used extensively in previous studies (Braco et al, 1990;Dabulis and Klibanov, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that ␤-elimination is a unimolecular reaction also facilitated the kinetic analysis, and the comparison with the catalytic antibodies and the polymers. BSA was selected for initial experiments as it was available in large quantities, inexpensive, and was used extensively in previous studies (Braco et al, 1990;Dabulis and Klibanov, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…It can be best illustrated by (bio)molecular imprinting, an approach which enables the introduction of new binding sites into protein molecules (Braco et al, 1990;Dabulis and Klibanov, 1992) and the alteration of an enzyme's catalytic properties such as activity (Mingarro et al, 1995), substrate specificity (Johnsson et al, 1995;O'Rich, and Dordick, 1997) or enantioselectivity (Stahl et al, 1990(Stahl et al, , 1991. However, if ligands can be employed to alter protein conformations in organic solvents in a predictable manner, it should be possible to use this approach for the induction of ''de novo'' catalytic activity in existing proteins via imprinting with transition state analogues (TSA) (Lerner et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This situation has allowed us to design a D-glucose-selective QCM resonator by a simple imprinting method. 45 More recently, it was shown that the molecular imprinting is achieved when one utilizes the reprecipitation process of functionalized ''soluble'' polymers [46][47][48] and the gel formation process of low molecular-weight gelators. 49 These new trends suggest the generality of the molecular imprinting concept: that is, the formation of 3-D cross-linked resins is not the sole way toward the molecular imprinting.…”
Section: Molecular Recognitionmentioning
confidence: 99%
“…In the case of pre cip i ta tion or liophilization of a the pro tein from aque ous en vi ron ment in the pres ence of a tem plate mol e cule, the lat ter can fur ther dem onstrate pre dict able changes of its prop er ties in or ganic sol vents [146][147][148][149][150][151][152][153][154][155][156][157], and (un der con di tion of ad di tional sta bi li za tion) in aque ous so lu tions [158]. Syn thetic recep tor sites can be also formed us ing the method of molec u lar im print ing in cross-linked car bo hy dratesstarch [159] and am y lase [160,161].…”
mentioning
confidence: 99%